2017
DOI: 10.18637/jss.v077.i10
|View full text |Cite
|
Sign up to set email alerts
|

NonpModelCheck: An R Package for Nonparametric Lack-of-Fit Testing and Variable Selection

Abstract: We describe the R package NonpModelCheck for hypothesis testing and variable selection in nonparametric regression. This package implements functions to perform hypothesis testing for the significance of a predictor or a group of predictors in a fully nonparametric heteroscedastic regression model using high-dimensional one-way ANOVA. Based on the p values from the test of each covariate, three different algorithms allow the user to perform variable selection using false discovery rate corrections. A function … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Investigators have found that a linear model taking log(Y ) as response and 4 out of the 8 covariates as predictors describe the data well (see [81,Section 9.4] and also [81,Section 10.6]). In particular, this linear model can be [5], VSURF [54], npvarselec [148], and MMPC [83] (all using their default settings). The selected variables, obtained by the different methods, are shown in Table 6.…”
Section: Surgical Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Investigators have found that a linear model taking log(Y ) as response and 4 out of the 8 covariates as predictors describe the data well (see [81,Section 9.4] and also [81,Section 10.6]). In particular, this linear model can be [5], VSURF [54], npvarselec [148], and MMPC [83] (all using their default settings). The selected variables, obtained by the different methods, are shown in Table 6.…”
Section: Surgical Datamentioning
confidence: 99%
“…It can be seen the variables selected by KFOCI (with 1-NN, 2-NN, 3-NN graphs) are very similar to those selected by the carefully analyzed linear regression approach 20 . Further, KFOCI selects the same set of variables as many well-implemented variable selection algorithms such as VSURF [54], npvarselec [148], and MMPC [83].…”
Section: Surgical Datamentioning
confidence: 99%